Agranulocytosis attributed to metamizole: An analysis of spontaneous reports in EudraVigilance 1985‐2017. Issue 2 (7th October 2019) - Hoffmann, Falk; Bantel, Carsten; Jobski, Kathrin
Abstract: Despite ongoing debates about its safety, the use of metamizole (dipyrone) is still increasing in many countries. In this study, we analysed spontaneous reports of suspected metamizole‐associated agranulocytosis recorded in EudraVigilance database from 1985 to 2017 with regard to patient and treatment characteristics as well as fatal vs non‐fatal outcomes and compared these findings among countries. A total of 1448 reports from 31 different countries were included (Germany 42.0%; Spain 29.6%; Switzerland 13.1%; other countries 15.3%). Mean age of patients was 53.6 years (63.4% females). Differences among countries were observed, for example with respect to patient age, route of administration and daily doses. Overall, median time between starting metamizole and developing an agranulocytosis was 13 days with 34.7% of cases occurring up to 7 days. This time was much shorter in patients who had already received metamizole before (median: 6 vs 15 days). About 16% of cases ended fatally. Patients with fatal outcomes were older and more often had also received methotrexate compared to those with non‐fatal outcomes. When adjusting for age and sex in a multivariable logistic regression, methotrexate was associated with an increased risk of fatal outcomes (odds ratio: 5.18; 95% confidence interval: 3.06‐8.78). In conclusion, metamizole‐associated agranulocytosis is still a life‐threatening condition, especially in the elderly and those also receiving methotrexate. As agranulocytosis can develop weeks after last administration and independently of dose and duration of treatment, prescribers and patients should be aware of its signs and symptoms.